Analysis of Elementary Mathematics Books Based on the Implementation of Guided Inquiry Model Process Skills - Abung, Miranda; Herman, Tatang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The inquiry learning model is one of the models set by the government as a learning model that uses a scientific approach. This study aims to analyze the book in terms of the working steps of the guided inquiry learning model. This research focused on the fourth-grade mathematics textbooks published by the Ministry of Education and Culture on fractions as the focus of the material. The data analysis technique was carried out in a qualitative descriptive manner with a documentation study by analyzing the material's content in the fourth-grade mathematics textbook. The analysis activities adapted to the activities of the guided inquiry learning model, which consists of orientation stages, conceptualization, investigations, conclusions, and discussions. The analysis results shown that the guided inquiry learning model activities that are mostly carried out in terms of application are conducting experiments to test hypotheses. These activities, if added up as much as 68 times throughout the six chapters of the book. The most minor activity carried out is the discussion activity. The activity was carried out 14 times throughout the six chapters provided by the book.